Law, Engineering, and the American Right-of-Way Imagining a More Just Street - Prytherch, David (Springer International Publishing, 2018)
This book explores the geography of the everyday roadway and contemplates how regulation and design shape our streets. People may question the hegemony of cars, but reimagining public streets is a major conceptual and technical challenge. Drawing from "new mobilities" and transport studies, Prytherch addresses how streets are structured by policy standards; what it means to have a right to the street; and how a more just street would look-in both theory and practice. He summarizes key traffic statutes, case laws, and engineering manuals, and interprets these in relation to mobility rights and justice. At its core, the book moves beyond criticism to highlight emerging movements which aim to develop more complete and livable streets for everyone.